2018
DOI: 10.3390/coatings8050160
|View full text |Cite
|
Sign up to set email alerts
|

The Functionalization of Nanostructures and Their Potential Applications in Edible Coatings

Abstract: Nowadays, edible coatings incorporated with nanostructures as systems of controlled release of flavors, colorants and/or antioxidants and antimicrobial substances, also used for thermal and environmental protection of active compounds, represent a gap of opportunity to increase the shelf life of food highly perishable, as well as for the development of new products. These functionalized nanostructures have the benefit of incorporating natural substances obtained from the food industry that are rich in polyphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 158 publications
(138 reference statements)
0
9
0
1
Order By: Relevance
“…Many researchers have concluded that the rate of oxygen consumption and the evolution of CO 2 and ethylene production during the packaging and storage of fruit play a major role in extending shelf life [3,7,[20][21][22][23][24][25]. Modified atmospheric packaging (MAP), controlled atmospheric packaging (CAP), and edible packaging have significantly controlled the deterioration of fruit for a longer period of time by maintaining the proper gaseous environment around the fruit [18,[26][27][28]. These technologies are aimed at reducing the respiration rate and transpiration rate and subsequently degrade the speed of biochemical reaction occurring during the storage of fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have concluded that the rate of oxygen consumption and the evolution of CO 2 and ethylene production during the packaging and storage of fruit play a major role in extending shelf life [3,7,[20][21][22][23][24][25]. Modified atmospheric packaging (MAP), controlled atmospheric packaging (CAP), and edible packaging have significantly controlled the deterioration of fruit for a longer period of time by maintaining the proper gaseous environment around the fruit [18,[26][27][28]. These technologies are aimed at reducing the respiration rate and transpiration rate and subsequently degrade the speed of biochemical reaction occurring during the storage of fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Dzięki temu możliwe będzie otrzymywanie modyfikowanych właściwości barierowych określonych produktów, walorów smakowo-zapachowych, a także zwiększenie ich wartości odżywczej. Obecnie brakuje przepisów, które jednoznacznie określą ryzyko związane ze stosowaniem nanomateriałów, lecz uznaje się, że wszystkie występujące skutki toksykologiczne zależą od parametrów fizykochemicznych stosowanych nanomateriałów [23].…”
Section: Zastosowanie Powlekania W Przemyśle Spożywczymunclassified
“…Thus, it is necessary to protect this fruit with technologies that reduce post-harvest losses [3]. In this regard, significant progress has been made in developing edible nano-coatings [4,5]. Modifying permeability to O 2 and CO 2 and adding active components that are capable of improving such properties as antioxidant and antimicrobial capacity can considerably reduce enzymatic and respiratory activity and, therefore, increase the shelf life of fresh-cut, ready-to-eat products [6].…”
Section: Introductionmentioning
confidence: 99%